Mampukah Budaya Organisasi Pemerintah Menyatukan Gen X, Gen Y dan Gen Z? - - Kasih, Pustika Chandra (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2023)
Gen X, Gen Y and Gen Z are labeling the name of a generation with a certain year of birth with the unique character of each. Differences in perspectives on how to conduct communication between superiors and subordinates in the position structure in this bureaucracy are interesting things to study. The theory of organizational culture is a reference in examining how these three generations interpret culture within the organization through the performances that occur in their work environment. The purpose of this research is to present a description of the intergenerational process of meaning forming organizational culture in the government work environment. The researcher chose an interpretive approach with the aim of observing the realities on the ground without generalizing all members of society. Qualitative research methods are presented with field data based on the results of in-depth interviews with employees who have the capacity to answer questions. In conclusion, organizational culture is defined differently from generation to generation. The differences in characters and perspectives of the three generations experience obstacles and cause conflict, but can still be resolved by adaptation and compromise. Technological developments have contributed to changes in organizational culture which are the result of the affiliation of Gen X, Gen Y and Gen Z in the government bureaucracy, especially in the Ministry of Public Works and Housing.